The value of assessment for learning in the teaching of physical education - André Moura; Ana Silva; Amândio Graça; Paula Batista (Federación Extremeña de Balonmano; University of Extremadura, 2021)
This study report a pedagogical experience focused on the use of assessment for learning principles in physical education during the school placement. The propose was to capture the value and meaning ascribed by preservice teachers and students involved on this study. Participated, four preservice teachers and 94 students on secondary education at two schools situated on the region of Porto. Preservice teachers' perceptions were collected through individual interviews, log diary and school placement report. Students' perceptions were collected through teaching artefacts (dossier, self and peer assessment forms) and focus group interviews. Data were triangulated and subject to a thematic analysis (Bardin, 2008), resulting in three main themes: instructional alignment, student-centred teaching, authentic learning. Findings show that: teaching-learning process was clear and shared among students and preservice teachers; preservice teachers acted as facilitators of the process while students acted as the main responsible; students learned on a personal and social level; and preservice teachers changed their teaching.